Investigating the effect of electronic government in realizing social justice in Iraq - Najm, Heidar; Tavallaee, Ruhollah (Bulletin of Social Informatics Theory and Application, 2018)
The increasing use of information technology, communication tools and applied programming has led to the development and evolution of public policies, processes, and functions. Information and communication technology is entering not only the provision of citizen services, but also public utilities, improving accountability and transparency in government performance, and saving government costs and government management. Developing countries are moving toward e-government, but in order to succeed in deploying e-government, cultural and institutional considerations must be taken into consideration. This is a survey research and the statistical population includes experts in e-government in Iraq. Therefore, using Morgan's table, 196 experts have been selected. To collect data, questionnaires were used. Through the study it was found that in terms of the development of the rule of law, Iraq's Missan Oil Company is in a good condition, and 55 percent of the respondents believed that the expansion of the rule of law, the behavior based on the principles and rules and avoiding to impose personal interests are the results of the deployment of e-government. Furthermore, according to the results and considering that out of six existing sub-hypotheses, 5 sub-hypotheses were confirmed, the main hypothesis of the research which is based on the effect of e-government on social justice is confirmed.